Diseño de un sistema contable agropecuario para la Asociación de Trabajadores Agrícolas San Antonio de Valencia. - Pinango Cuatucuago, Klever Patricio (2020)
This integrating project was directed to the development of an Agricultural Accounting System, for the San Antonio de Valencia Agricultural Workers Association in order to control the activity of milk production and biological assets of the association, identifying the accounting and financial information which was carried out through bibliographic research in reliable sources and in different academic repositories, used for the concepts, objectives and types of agricultural accounting and the regulations applicable to IFRS for SMEs, through the application of process mapping, control sheets internal, the diagnosis of the Association and incorporating the descriptive, inductive, deductive, quantitative and qualitative methodologies that made the selected accounting records, for the collection of data information and detect the existing shortcomings at the time of performing each of the activities in milk production. For the design and implementation of the accounting system, we proceeded to collect and organize all the accounting information for its registration, the classification and respective presentation of the economic transactions in order to analyze them, know the economic and financial situation of the Association, for the taking of adequate decisions and to improve the financial process, applying through a chart of accounts according to the needs.